INTERNATIONAL TRADE DISPUTE SETTLEMENT THROUGH DISPUTE SETTLEMENT BODY (DSB) AND INTERNATIONAL ARBITRATION BODY - Supeno, Supeno (Nurani, 2020)
The current trend in international trade is growing rapidly, along with these developments, the problems occurring in trade transactions are also increasing on the other hand the disputes arising in international trade are also increasing, under such conditions it is necessary to have greater legal role to overcome international trade issues. Several international trade dispute settlement institutions have been established but have not been well known and maximized in resolving international trade disputes whereas dispute settlement institutions play a huge role in the effort to create economic stability and world trade. Dispute resolution agencies that need special attention are Dispute Settlement Body and International Arbitration. In this article author using the goodfaith theory as the importand principle in the dispute dispute of international business. The author would like to disclose some international trade dispute settlement which becomes the choice for disputing countries so that the writer can formulate the following problem of Settlement of international trade disputes through the Dispute Settlement Body (DSB) of the World Trade Organization (WTO) and international trade disputes through international arbitration bodies. Keywords: international trade dispute, dispute settlement, Arbitration